Mental Health System Development: from Policy to Practice - Piyakulmala, Tiwawan; Suttipapar, Teerapat (Journal of Health Science of Thailand, 2020)
The aims of this study were to develop a mental health service system under the Kalasin provincial context. A research and development methodology was conducted from October 2018 to November 2019. The study comprised 3 main elements: (1) conducting a situation analysis on service provision and readiness of health personnel; (2) developing the appropriate service guideline and supporting health personnel to implement; and (3) monitoring and evaluation for improvement of service provision. A purposive sampling technique was applied to select 236 mental health personnel from all health facilities of Ministry of Public Health in the province. The data collection tools consist of the evaluation forms of mental health service key performance indicators (KPIs) and assessing the readiness of health personnel. Descriptive statistics and content analysis were used for analyzing the data. The results showed that some of the KPIs were not achieved. The health personnel as measure with their self-efficacy towards the scope and performance of psychiatric and mental health showed moderate level of readiness. Therefore, the researchers established a guideline as an intervention to improve mental health service. Activities for strengthening competency of health personnel were introduced including training, focus group discussions, establish platform for knowledge sharing, coaching, and promoting local network partnerships. After 6 months of the guideline implementation, the perception, expectation and practices of health personnel according to the scope and competency of psychiatric and mental health practice were improved. Furthermore after 12 months, the relapses of schizophrenia patients from the same disease within three months decreased by 3.02%. The re-admission rate of psychiatric patients within 3 months also decreased by 1.58%. Whereas, 27.00% improvement was observed in the follow-up visits and ongoing care among the psychiatric patients with complex problems. Additionally, the rate of access to major depression services was increased by 19.37%. In conclusion, the overall performance met the criteria of KPI standard.